Responsabilidad social empresarial y su relación con la competitividad de las MYPES de Iquitos 2024 - Pezo Galvez, Hector Gilberto (2025)
The purpose of this research was to determine how corporate social responsibility is related to the competitiveness of MSEs in Iquitos, 2024. A non experimental, cross-sectional and basic design was used, applying questionnaires to a sample of 30 MSEs. The results showed that the perception of Corporate Social Responsibility (CSR) is at a high level, as 46,7% of respondents said they totally agreed with its implementation. As for the Competitiveness variable, a high level was identified, with 53,3% of the employees saying that they strongly agree that it is promoted in their work environment. In addition, Spearman's Rho test showed a moderate positive correlation of rho=0,681 and a significance of 0,030 <0,05, indicating that CSR is significantly related to competitiveness.